FUNDAMENTALS OF SPEECH CULTURE AND PUBLIC SPEAKING (Conferencea, 2022)
In linguistics, it is not consistent to divide the concept of speech culture into the concept of language culture and speech culture. In general, these two concepts are mainly used together or mixed with the term speech culture or language culture.